A green supply chain network design framework for the processed food industry: Application to the orange juice agrofood cluster. (July 2017) - Miranda-Ackerman, Marco A.; Azzaro-Pantel, Catherine; Aguilar-Lasserre, Alberto A.
Highlights: Food sourcing from organic and conventional suppliers is integrated into the modelling approach. Multi-level decision making is formulated as a network of choices from technology selection to plant location. It allows for the evaluation of multiple decision scenarios based on objectives and preferences. Output in terms of multiple criteria can reflect antagonistic objectives and preferences. The case study demonstrates a potential improvement environmental performance over conventional supply chain design approach. Abstract: Food production has put enormous strain on the environment. Supply chain network design provides a means to frame this issue in terms of strategic decision making. It has matured from a field that addressed only operational and economic concerns to one that comprehensively considers the broader environmental and social issues that face industrial organizations of today. Adding the term "green" to supply chain activities seeks to incorporate environmentally conscious thinking in all processes in the supply chain. The methodology is based on the use of Life Cycle Assessment, Multi-objective Optimization via Genetic Algorithms and Multiple-criteria Decision Making tools (TOPSIS type). The approach is illustrated and validated through the development and analysis of an Orange Juice Supply Chain case study modelled as a three echelon GrSC composed of the supplier, manufacturing and market levels that in turn are decomposed into more detailed subcomponents. Methodologically, the work has shown the development of the modelling and optimization GrSCM framework is useful in the context of eco-labelled agro food supply chain and feasible in particular for the orange juice cluster. The proposed framework can help decision makers handle the complexity that characterizes agro food supply chain design decision and that is brought on by the multi-objective nature of the problem as well as by the multiple stakeholders, thus preventing to make the decision in a segmented empirical manner. Experimentally, under the assumptions used in the case study, the work highlights that by focusing only on the "organic" eco-label to improve the agricultural aspect, low to no improvement on overall supply chain environmental performance is reached in relative terms. In contrast, the environmental criteria resulting from a full lifecycle approach is a better option for future public and private policies to reach more sustainable agro food supply chains.